High voltage ratio interleaved boost DC-DC converter for high power fuel cell application - Samosir, Ahmad Saudi (Praise Worthy Prize, 2011)
The application of fuel cell is increasing in the last years mainly due to the possibility of high efficient decentralized clean energy generation. Fuel cells are a potential power source for electric vehicle or distributed power generation system. In electric vehicle application, a high power boost dc-dc converter is adopted to adjust the output voltage, current and power offuel cell engine to meet the vehicle requirements. The major challenge of designing a boost converter for high power application is how to handle the high current at the input and high voltage at the output. In this paper, a high voltage ratio interleaved boost dc-dc converter is proposed for stepping-up the voltage on high power application. A prototype of converter system was built. The experimental waveforms of the high voltage ratio interleaved boost converter are presented.